Improvement of a convertible undeniable partially blind signature scheme - Han, Song; Chang, Elizabeth; Dillon, Tharam S.; Wang, J. (IEEE Computer Society Press, 2006)
Undeniable signatures are the digital signatures that should be verified with the help of the signer. A signer may disavow a genuine document, if the signature is only verifiable with the aid of the signer under the condition that the signer is not honest. Undeniable signatures solve this problem by adding a new feature called the disavowal protocol in addition to the normal components of signature and verification. Disavowal protocol is able to prevent a dishonest signer from disavowing a valid signature. In some situations, an undeniable signature should be converted into a normal digital signature in order that the signature can be universally verified. Blind signatures are the digital signatures that help a user to get a signature on a message without revealing the content of the message to a signer. For the blind signatures, if the signer is able to make an agreement with the user, then the underlying signer may include some common information that is known to the user, then such signatures are partially blind signatures. Convertible undeniable partially blind signatures are of the features of undeniable signatures, blind signatures, convertible undeniable signatures, and partially blind signatures. Recently, a convertible undeniable partially blind signature scheme was presented. In this paper, we first analyse a security flaw of the convertible undeniable partially blind signature scheme. To address the security flaw, we present an improvement on the disavowal protocol. The improved scheme can prevent the signer from either proving that a given valid signature as invalid, or cheating the verifier.